Assessing the Effect of Occupational Health and Safety Practices on Employee Performance at Snaptec (U) Limited - Noella Mwebaza (Uganda Christian University, 2026)
This research investigates the critical effect of occupational health and safety practices on employee performance within Uganda’s construction sector, specifically focusing on Snaptec (U) Limited in the central region of Uganda. The construction industry is essential for socio-economic development but remains one of the most hazardous sectors globally and locally, often characterized by low compliance with safety regulations like the Ugandan Occupational Safety and Health Act of 2006. Grounded in Herzberg’s two-factor theory, the study categorizes OHS practices as fundamental “hygiene factors” that are necessary to prevent job dissatisfaction and support high productivity. The research specifically evaluates three OHS variables: the implementation of safety policies and procedures, the provision of personal protective equipment (PPE), and the effectiveness of safety training and awareness programs. Using a mixed methods approach with a case study design, data was gathered from a diverse sample of 29 participants, including project managers and casual laborers, through structured questionnaires and in-depth interviews. The findings demonstrate that proactive safety management significantly enhances employee morale, commitment, and job satisfaction while reducing absenteeism and project delays. However, the study also identifies significant implementation gaps, such as inconsistent PPE supplies and inadequate safety drills, which hinder optimal performance. The dissertation concludes that strategic investment in OHS is not merely a regulatory requirement but a vital driver for organizational competitiveness and worker well-being. It recommends that construction firms in Uganda prioritise robust safety cultures and that policymakers strengthen enforcement mechanisms to ensure a safer and more
Undergraduate research